Accuracy Of Colour Doppler Ultrasonography In Differentiating Benign From Malignant Thyroid Nodules - Mahesh kumar; Kelash Kumar; Ghazala Shahzad; Bhesham Kumar (Pakistan Journal of Medicine and Dentistry, 2024)
Background: